Effects of furosemide on the hearing loss induced by impulse noise - Kriksunov Leonid; Weinberger Jeffrey M; Adelman Cahtia; Sohmer Haim (Journal of Occupational Medicine and Toxicology, 2011)
Abstract Background The permanent hearing loss following exposure to intense noise can be due either to mechanical structural damage (tearing) caused directly by the noise or to metabolic (biochemical) damage resulting from the elevated levels of free radicals released during transduction of the sound overstimulation. Drugs which depress active cochlear mechanics (e.g. furosemide and salicylic acid) or anti-oxidants (which counteract the free radicals) are effective in reducing the threshold shift (TS) following broadband continuous noise. This study was designed to determine whether furosemide can reduce the TS following exposure to impulse noise, similar to its action with continuous broadband noise. Methods Shortly after furosemide injection, mice were exposed to simulated M16 rifle impulse noise produced by different loudspeakers and amplifiers in different exposure settings and, in other experiments, also to actual M16 rifle shots. Results Depending on the paradigm, the simulated noises either did not produce a TS, or the TS was reduced by furosemide. The drug was not effective in reducing TS resulting from actual impulse noise. Conclusion Simulated M16 rifle impulse noise may not truly replicate the rapid rise time and very high intensity of actual rifle shots so that the TS following exposure to such noise can be reduced by these drugs. On the other hand, actual M16 impulse noise probably causes direct (frank) mechanical damage, which is not reduced by these drugs.